(untitled) (Web of Teachers: Inderscience Research, 2025)
This article focuses on the specifics of the process of actors working on behavioral exercises with imaginary objects and the importance of the actor’s imagination and fantasy in the training of actors. In the article, the process of working on behavior exercises with imaginary objects of the students of the 1st year variety acting art education is given as an example. This article, which explores the development of the fantasy of a variety actor and the concept of norms, emphasizes the process of working on exercises and observations that form the basis of the profession.